2023
DOI: 10.1002/chem.202202902
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Evolution by a De Novo Designed Metalloprotein that Undergoes Ni‐Mediated Oligomerization Shift

Abstract: De novo metalloprotein design involves the construction of proteins guided by specific repeat patterns of polar and apolar residues, which, upon self-assembly, provide a suitable environment to bind metals and produce artificial metalloenzymes. While a wide range of functionalities have been realized in de novo designed metalloproteins, the functional repertoire of such constructs towards alternative energy-relevant catalysis is currently limited. Here we show the application of de novo approach to design a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The solid-state peptide synthesis was performed using a CEM Liberty Blue (Matthews, NC, USA) automated microwave peptide synthesizer as per our earlier reports [ 24 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The solid-state peptide synthesis was performed using a CEM Liberty Blue (Matthews, NC, USA) automated microwave peptide synthesizer as per our earlier reports [ 24 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Attachment of the ruthenium complex to NiRd was provided through a native free cysteine residue, close to the metal-binding site. The effective distance between the nickel center and the photosensitizer was modulated Inspired by the nickel center of [NiFe]-hydrogenases, Chackraborty and coworkers recently developed artificial metalloenzymes by engineering a tetrathiolate nickel center (NiS 4 ) into de novo designed coiled coils [244,245]. In their first study, self-assembly of two de novo peptides, each bearing a CXXC motif, in the presence of nickel(II) yielded a two-stranded coiled coil (2SCC) enclosing the NiS 4 site (Figure 10b and Table 2, entry 38) [244].…”
Section: Peptide-and Protein-based Catalytic Systemsmentioning
confidence: 99%
“…Spectroscopic studied revealed that a precise acidity is required for activity, suggesting that the protonation state of Cys is crucial for H 2 production. In the latest study, a peptide sequence was designed to favor a four-stranded coiled coil (4SCC), and the presence of a rubredoxin-like CXXC motif in each peptide strand was conceived to provide a dual nickel-binding site (Table 2, entry 39) [245]. Interestingly, nickel binding induced an oligomerization shift, stabilizing the formation of dimers, while the apo form was predominantly trimeric.…”
Section: Peptide-and Protein-based Catalytic Systemsmentioning
confidence: 99%